Analisis Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Pada Perusahaan Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia (Studi Kasus Pada Tahun 2010-2014) - Santoso, Eko, Drs. Ma'ruf, MM (2016)
This research aims to determine the effect of Loan to Deposit Ratio (LDR), Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), Return on Asset (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Operating Profit Margin (NPM) to Price Book Value (PBV). The greater the stock price, the higher the value of the company and prosperity of the shareholders of the company. Population in this research are all banking companies listed in Indonesian Stock Exchange. Hypotthesis testing is done with tool SPSS (Stastical Product and Servive Production). The results showed, t-test variable DAR, DER, ROE dan NPM has an influence on the variable PBV. While variable ROA, OPM and LDR has no influence on the variable PBV. F test result indicate the variabel DAR, DER, ROA, ROE, OPM, NPM and LDR has the simultant effect of the variabel PBV. Price Book Value is able to be explained by the variable DAR, DER, ROA, ROE, OPM, NPM and LDR by 59% and the remaining 41% is explained by other variables outside this research.